REKONSTRUKSI TEORI PEMBELAJARAN MOHAMMAD SYAFEI: DINAMIKA DAN RELEVANSINYA DI ERA MODERAN - Hariadi, Farhan; Dozan, Wely (JURNAL AL-QAYYIMAH, 2022)
Education is an intellectual heritage that must be used as the main container in shaping humans into human beings (insan al-kamil), namely full-fledged humans in accordance with Islamic principles. Therefore, this effort must be implemented through the learning theory of the educational process according to the planned targets. This study examines the thoughts of one of the Indonesian figures, Syafei's learning theory, through his educational thought which gave birth in Kayutanam which was named Indonesische Nederlandsce School (INS). There are several basic aspects as the formulation of the problem in this research including, First, how the concept of learning theory was initiated by Mohammad Syafe'i. Second, how to actualize the concept of learning, especially in this modern era. The type of research is a literature study that is descriptive analysis, namely examining his thoughts through various books, journals, and references that are relevant to the research. In particular, the concept of learning theory at this time by looking at the learning theory of an educational figure from Indonesia before independence. By knowing the concept of the character's thinking about learning that is practiced, it is expected to be able to develop new concepts from old concepts in education. Mohammad Syafei, an Indonesian education leader who prioritizes learning and work-based schools. Teaching and education in schools must be based on the needs of the community, schools are a living part of society, especially in today's modern era and how relevant their thinking is in this modern era.